2017
DOI: 10.1148/radiol.2016160874
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific Hip Fracture Strength Assessment with Microstructural MR Imaging–based Finite Element Modeling

Abstract: Purpose To describe a nonlinear finite element analysis method by using magnetic resonance (MR) images for the assessment of the mechanical competence of the hip and to demonstrate the reproducibility of the tool. Materials and Methods This prospective study received institutional review board approval and fully complied with HIPAA regulations for patient data. Written informed consent was obtained from all subjects. A nonlinear finite element analysis method was developed to estimate mechanical parameters tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…CT is not the only medical imaging technique able to quantify vBMD. MRI-images, though not as suited to estimate bone density as CT-images [150,277], were used to accurately quantify in vivo vBMD of a patella by [278] and to estimate CLE-properties [48,131].…”
Section: Patient-specific Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…CT is not the only medical imaging technique able to quantify vBMD. MRI-images, though not as suited to estimate bone density as CT-images [150,277], were used to accurately quantify in vivo vBMD of a patella by [278] and to estimate CLE-properties [48,131].…”
Section: Patient-specific Mechanical Propertiesmentioning
confidence: 99%
“…Terms such as nonlinear analysis may be misleading. For instance, [99,101,131] speak of non-linear analysis, but do not specify the type or source of non-linearity. There are mainly four types/sources of non-linearity in a solid continuum mechanics problem [302] (p. 85), [303] (p. 8): (1.)…”
Section: Remark 25 (Misleading Term-nonlinear Analysis)mentioning
confidence: 99%
“…Finally, Rajapakse et al showed that it is now possible to assess MRI‐based strength measures at the level of the whole proximal femur with high reproducibility in vivo using nonlinear FEA . Median CVs/ICCs for the several parameters computed including yield strain, yield load, ultimate strain, ultimate load, resilience, and toughness were <8% with ICCs of 0.99.…”
Section: Mri Of Bone Microarchitecture For Assessment Of Fracture Rismentioning
confidence: 99%
“…In addition to correlating bone strength with its microarchitecture, bone mechanical properties assessed by FEA may provide information about skeletal fragility and fracture risk, independent of BMD or architecture measurements, and add another potential method of assessing bone vulnerability . Recently Rajapakse et al described a reproducible FEA method by using MRI to estimate mechanical parameters that relate to hip fracture resistance. This method is an attractive future proposition, and particularly relevant to a population with advanced CKD and high rates of hip fractures…”
Section: Introductionmentioning
confidence: 99%